Prospective design scenarios for Science, Technology and Innovation 2040 - Rodríguez Figueroa, José Julio (2013)
This research related with the design of scenes concerned with science, technology and innovation will identify the main problem as the gap that exists between Peru and LatinAmerican countries of investment in ST + I as a percentage of gross domestic product. In Peru you may see that the investments only 0.15% while in other countries, may quintuplicate and generating a gap that must be filled with plans and strategic management of science, technology and innovation. The hypothesis suggests that it is possible to design scenes for the proper management of public policies aimed at closing the differentiation of Peru with the countries of Latin America, which is the objective of the study. For the design of scenes and futuristic trends, the Delphi method will be used through choose experts will be asked about the futureof ST+ Ithen analyzed the responses to the questionnaires and prepare the desired questionnaire prospective methodology. Visualizing the gap closing scientific, technological and innovation in relation to the countries of Latin America.